ANTICIPATING RANGE LAND DEVELOPMENT IN THAL (PUNJAB) - A. A. Chaudhry; M. S. Haider; M. Mushtaque; J. Ahsan; M. Ali (Journal of Animal and Plant Sciences, 2012)
A survey was conducted to assess the prospects of rangeland development in Thal tract of Punjab, Pakistan. At local level 64 respondents comprising 16 each of large, medium, small landholders and landless respondents were interviewed. Range personnel working in the tract were also interviewed. The number of livestock kept by respondents was highly correlated with the size of landholdings. Major source of income was livestock rearing. For grazing purpose, the dependence of respondents on vegetation of govt. rakhs varied from 94 to 100 percent. More than 41 percent forage requirements of livestock of all respondents remain unmet after grazing. Majority of graziers were facing problems like low carrying capacity of rakhs, lack of drinking water and protection measure forced by the Forest Department. The major constraints in range development efforts were lack of funds, and disinterest of range personnel working in the field. Other constraints were half hearted implementation of existing range management regulation and inadequate research.
Keywords: Range management; Respondents; Range personnel; Grazing problems; Livestock feeding; Thal